2018
DOI: 10.1186/s13012-018-0801-2
|View full text |Cite
|
Sign up to set email alerts
|

A description of health care system factors in the implementation of universal weight management services for children with overweight or obesity: case studies from Queensland and New South Wales, Australia

Abstract: BackgroundThe prevalence of childhood obesity poses an urgent global challenge. The World Health Organization (WHO) Commission on Ending Childhood Obesity recommends the provision of appropriate family-based, lifestyle weight management services through universal health care to support families of children with overweight or obesity; however, there are few examples of their implementation ‘at scale’. The purpose of this research was to compare and contrast the impact of system and organisational factors on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…The importance of co‐design for effective health interventions has been documented previously, 38,39 and our findings support this. Collaboration and co‐design with existing stakeholders, health services and governments were pointed out throughout the interviews as key to the success of the EPOCH interventions and their translation efforts.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The importance of co‐design for effective health interventions has been documented previously, 38,39 and our findings support this. Collaboration and co‐design with existing stakeholders, health services and governments were pointed out throughout the interviews as key to the success of the EPOCH interventions and their translation efforts.…”
Section: Discussionsupporting
confidence: 88%
“…The present results add to the growing body of evidence examining factors that need to be considered when designing an intervention to be delivered at scale. Specifically, our findings align with previous research by emphasising the need to ensure that facilitators are appropriately trained, key messages are repeated throughout a program and delivery occurs across childhood to avoid fade‐out effects of health gains 37,38 . A key message from the interviews was the need to seamlessly align the intervention with other efforts to prevent childhood obesity.…”
Section: Discussionsupporting
confidence: 81%
“…In the research sphere, we found few studies that used the scalability tools identified in the peer-reviewed literature (Cambon et al , 2013; Milat et al , 2016) to consider the question of scalability of an intervention. Such studies were either retrospective case studies using the tool as an analytical framework (Trompette et al , 2014; Vidgen et al , 2018), or trial protocols proposing a qualitative implementation study or process evaluation focused on scale-up, running in parallel or at the end of the study (Kabore et al , 2016; Lonsdale et al , 2016). However, these are yet to generate evidence on the success of scaling-up strategies, as advocated by previous reviews (Ben Charif et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Those standardized constructs provide an approach to articulate the determinants of implementation success and a guide to identify factors that are most important to implementation [ 30 ]. A body of qualitative and mixed-method studies have adopted CFIR to develop interview guides [ 32 ], form codebooks [ 33 ], analyze and interpret data [ 34 ], and report implementation-related findings [ 29 ]. These reports provide strong support for incorporating CFIR constructs when identifying multilevel factors that facilitate or hinder implementation, including the implementation of exercise programs for rural CSs [ 33 37 ].…”
Section: Introductionmentioning
confidence: 99%